2017
DOI: 10.1016/j.chiabu.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a parenting program to reduce the risk of child maltreatment in South Africa

Abstract: Parenting programs in high-income countries have been shown to reduce the risk of child maltreatment. However, there is limited evidence of their effectiveness in low- and middle-income countries. The objective of this study was to examine the initial effects of a parenting program in reducing the risk of child maltreatment in highly-deprived and vulnerable communities in Cape Town, South Africa. Low-income parents (N=68) with children aged three to eight years were randomly assigned to either a group-based pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 76 publications
(32 reference statements)
2
54
0
Order By: Relevance
“…The data were analyzed using the framework approach, which was designed for applied policy research and is particularly suitable for research with specific questions focused on a priori issues. 30 The framework approach involves a five step process: (1) reading and rereading the transcripts, (2) identifying themes and subthemes and constructing an index of codes grouped into categories, (3) applying the codes to the individual transcripts, (4) rearranging the data in charts of each theme and/or subtheme with entries for each respondent under each theme, and (5) examining the charts to identify the key characteristics of the data. One research assistant applied the codes to the data and prepared the thematic charts.…”
Section: Qualitative Interviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data were analyzed using the framework approach, which was designed for applied policy research and is particularly suitable for research with specific questions focused on a priori issues. 30 The framework approach involves a five step process: (1) reading and rereading the transcripts, (2) identifying themes and subthemes and constructing an index of codes grouped into categories, (3) applying the codes to the individual transcripts, (4) rearranging the data in charts of each theme and/or subtheme with entries for each respondent under each theme, and (5) examining the charts to identify the key characteristics of the data. One research assistant applied the codes to the data and prepared the thematic charts.…”
Section: Qualitative Interviewsmentioning
confidence: 99%
“…Training young children's caregivers in appropriate child behavior management strategies and in how to provide a secure and nurturing environment can reduce harsh caregiving and reduce violence against children . There are a number of recent studies of violence prevention programs implemented with parents of young children in low‐ and middle‐income countries . However, less focus has been given to school‐based violence prevention programs in low‐ and middle‐income countries (LMICs), especially in the early childhood years .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The program was tested in a pilot RCT, which suggested that although the program had promise, revisions might strengthen its impact and feasibility (Lachman, Cluver, et al., ; Lachman et al., ). Content on positive reinforcement and discipline was subsequently refined, and additional training was provided to facilitators to strengthen competency in the collaborative process and in understanding social learning theory.…”
Section: Introductionmentioning
confidence: 99%
“…In the area of child maltreatment, parent training programs including parent-infant home-visiting programs and group parent-training programs for parents of older children, have demonstrated effectiveness for reducing child maltreatment in other contexts [ 61 , 62 ]. Importantly, several parent training programs have demonstrated cost-effectiveness for reducing child maltreatment in high-income countries such as the USA and are showing promise in South Africa [ 63 , 64 ]. Such programs should urgently be introduced into low- and middle-income contexts, such as South Africa, and their cost-effectiveness investigated in the new contexts, as a tool for advocating with governments for their use.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%